Eurosieroctwo seniorów a jakość ich życia – nowe wyzwania dla pedagogiki społecznej - Gaweł, Anna; Madej-Babula, Magdalena; Urlińska, Maria Marta (Wydawnictwo Naukowe UAM, 2014)
Taking on the issue of the quality of human life at a senior age requires the adoption of a particular perspective to recognizing the phenomenon of old age. It is in fact a phenomenon extremely diverse, multifaceted, involving closely related aspects of the biological, social and psychological, and its course is conditioned by the convolution of a variety of factors. One of them is the emigration of young people, who leave their parents alone in the home country and in fact make them Euroorphans. Job migration of adult children is a critical event in the lives of seniors and thus has a significant impact on their life quality. It is treated as a cognitive-emotional category associated with the environmental context of their daily activities. The phenomenon of Euro-orphanhood of seniors generates new lines of research in the field of social pedagogy. Contribution to them is mentioned in the article as a comparative research project.
Senior’s Euro- Orphanhood and Quality of Life: New Challenges for Social Pedagogy
Keywords: old age; labor migration; Euro-orphanhood; quality of life